Titanium oxide / carbon nanotube / graphene composite material and preparation method and application thereof

Ti4O7/carbon nanotube/graphene composite materials were prepared through hydrothermal reaction and high-temperature heat treatment, and the sandwich structure was prepared using hot pressing and supercritical foaming technology, which solved the problem of uncontrollable preparation process of titanium oxide-based electromagnetic shielding materials and the difficulty in designing multi-layer structures, and achieved efficient electromagnetic wave shielding performance.

CN119750640APending Publication Date: 2025-04-04NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054813.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The titanium oxide preparation process in titanium oxide-based electromagnetic shielding materials is uncontrollable, the multi-layer structure design is difficult, the absorption loss is low and the frequency band is narrow.

Method used

TiO2/carbon nanotubes/graphene precursors were prepared through simple and clean hydrothermal reaction, and then Ti4O7/carbon nanotubes/graphene composites were obtained through high-temperature heat treatment. Finally, the sandwich structure Ti4O7/carbon nanotubes/graphene electromagnetic shielding composites were prepared by hot pressing and supercritical foaming technology.

Benefits of technology

It realizes high-efficiency electromagnetic wave shielding material with ultra-low reflectivity, and improves electromagnetic shielding performance, especially in terms of narrow frequency bands and absorption losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750640A_ABST
    Figure CN119750640A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium oxide / carbon nanotube / graphene composite material as well as a preparation method and application thereof, and relates to the technical field of electromagnetic shielding materials. The method comprises the following steps: dispersing isopropyl titanate, acetic acid, carbon nanotubes and graphene in absolute ethyl alcohol, and uniformly mixing to obtain a mixed solution; transferring the mixed solution into a reaction kettle, and keeping the temperature at 160-200 DEG C for 4-8 hours to obtain a precursor; the precursor is subjected to heat preservation for 4 h at the temperature of 1000 DEG C in the hydrogen atmosphere, and the titanium oxide / carbon nano tube / graphene composite material is obtained. According to the invention, a TiO2 / carbon nanotube / graphene precursor is prepared through a simple and clean hydrothermal reaction, and then the Ti4O7 / carbon nanotube / graphene composite material is obtained through high-temperature heat treatment. Ti4O7 has relatively strong interface polarization and defect polarization capabilities, so that an efficient electromagnetic wave shielding material with ultralow reflectivity can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic shielding materials, and in particular to a titanium oxide / carbon nanotube / graphene composite material and a preparation method and application thereof. Background Art

[0002] Due to the rapid development of electronic devices and communication equipment, serious electromagnetic interference problems will inevitably occur, which will seriously affect the functions of nearby valuable electronic devices and cause information leakage. Moreover, electromagnetic pollution inevitably has a negative impact on humans. To solve this problem, we need to explore advanced electromagnetic shielding materials to eliminate or reduce electromagnetic pollution. Generally, when an electromagnetic wave encounters a material, it will experience reflection, absorption and transmission. Electromagnetic shielding materials block electromagnetic waves by reflection or absorption. In a homogeneous system, electromagnetic waves will be attenuated by corresponding polarization, conduction loss and scattering through the interaction of radiation with dipoles, free carriers, defects or impurities. In addition, in a heterogeneous structure system, the presence of interfaces between the various phases will cause additional dissipation of electromagnetic waves, and the poor impedance matching between the various components will cause such interface scattering. In a variety of media, a variety of scattering mechanisms act on electromagnetic shielding, resulting in the dissipation of electromagnetic waves. Generally, various forms of metals (metal sheets / films, foam metals, metal coatings, etc.) are used as conventional electromagnetic shielding materials. However, metal shielding materials have major disadvantages, such as high density, easy corrosion and expensive processing; at the same time, the EMI shielding mechanism is mainly determined by reflection, which will cause secondary EMI pollution, so shielding materials with high absorption rate must be used.

[0003] Among all the suitable candidate materials, a high dielectric constant Ti4O7 ceramic particle called "Magnéli phase titanium dioxide" is popular in many applications because of its narrow band gap and high conductivity. Magnéli phase titanium oxide contains different compounds with the general formula Ti n O 2n-1 (4≤n≤10), which can generally be obtained by heat treatment in an inert gas. n O 2n-1 In the case of Ti4O7, there is an oxygen deficiency in each n-layer. This special structure causes these materials to exhibit high electrical conductivity, which varies with the value of 'n'. However, as far as we know, Ti4O7 is mainly used in electrochemical fields such as batteries, electrometallurgy, electroplating, environmental protection and water treatment and cathodic protection. There are few reports on the application of Ti4O7-based composites in the field of electromagnetic shielding.

[0004] In addition, carbon materials (such as carbon black, graphene and carbon nanotubes (CNTs)) have excellent performance due to their high aspect ratio and large specific surface area, and they can be used as conductive fillers to efficiently manufacture electromagnetic shielding materials. At the same time, the formation of high conductivity and strong interface polarization will promote electromagnetic shielding performance. In particular, carbon materials have broad prospects in electromagnetic interference shielding applications due to their excellent corrosion resistance, electrical conductivity, low density and easy processing.

[0005] The prior art discloses a method for preparing a graphene / carbon nanotube electromagnetic interference shielding film, wherein a graphene oxide suspension, carbon nanotube particles and deionized water are mixed and stirred, wherein the mass fraction of carbon nanotubes in the carbon nanotube / graphene oxide solution is 5%, 10%, 15%, 20%, 30% and 40%, respectively. The uniformly mixed graphene oxide / carbon nanotube aqueous solution is cast on a polymethyl methacrylate substrate to form a hydrogel film with a thickness of 3 mm, and air-dried at room temperature for several days to obtain a graphene oxide / carbon nanotube film. The graphene oxide / carbon nanotube film is chemically reduced with hydroiodic acid to obtain a reduced graphene oxide / carbon nanotube film. Finally, the reduced graphene oxide / carbon nanotube film is annealed at 2800°C and mechanically compressed for 12 hours to obtain a dense graphene oxide / carbon nanotube film. However, the preparation method is complicated, the reduced graphene oxide / carbon nanotube film has a single component, and the electromagnetic shielding ability is limited. When the film thickness is 3 mm, the maximum electromagnetic shielding value of the reduced graphene oxide / carbon nanotube film is only 60 dB, and the corresponding conductivity is 2.74*10 5 S / m.

[0006] The prior art also discloses a method for preparing a carbon nanotube / zinc oxide / carbon fiber composite material, which heat treats a carbon fiber cloth (CF) in a muffle furnace at 400°C for 1 hour, and then transfers it to an acetone solution and soaks it for 12 hours to remove the sizing agent on the CF surface. 0.8g of dopamine hydrochloride is added to a mixed solution of 300mL of tris(hydroxymethylaminomethane) (10mmol / L, pH 8.5) and 100mL of anhydrous ethanol, and stirred to prepare a dopamine mixed solution. The carbon fiber from which the sizing agent has been removed is immersed in the dopamine solution and reacted at room temperature for 10 hours to obtain a polydopamine grafted carbon fiber. It is added to a ZnO seed solution prepared by mixing 2.2g of zinc acetate dihydrate with 500mL of isopropanol, annealed at 150°C to precipitate ZnO seed crystals, and repeated 3 times to obtain a CF fully coated with a ZnO seed layer. 0.05 mol / L zinc nitrate hexahydrate and 0.05 mol / L hexamethylenetetramine aqueous solution were uniformly mixed, and polyethyleneimine solution was added dropwise to adjust the pH value of the mixed solution to 7-8 to obtain a ZnO growth solution. CF coated with ZnO seed crystals was added to the ZnO growth solution and reacted at 90°C for 6 hours to obtain CF with surface-grown ZnO nanowires. 0.25 g ferrocene, 0.07 g thiophene and 9.1 g toluene were mixed to prepare a catalyst precursor solution. The precursor solution was heated to 1100°C under an argon atmosphere, the gas flow was switched to 7000 sccm hydrogen and 8.25 sccm ethylene, and the catalyst precursor solution was injected into the tube furnace at a rate of 0.6 mL / h using a syringe pump to grow carbon nanotubes. The ZnO-modified carbon fiber cloth was fixed on a stainless steel filter, and then placed at the tail gas end of the tube furnace to collect CNTs, which were filtered and deposited for 30 minutes to obtain a CNT / ZnO / CF composite material. The preparation process of the CNT / ZnO / CF composite material is complicated, and the electromagnetic shielding effectiveness is low, which is only 50 dB.

[0007] In order to provide a high thermal conductivity electromagnetic shielding carbon nanofilm, a person skilled in the art performs a stretching orientation treatment on a planar carbon nanofilm at a stretching rate of 0.1-100 mm / min, then performs an annealing treatment at a temperature of 800-3000°C and keeps the temperature for 1-3 hours, and then performs a calendering treatment at a pressure of 10-70 MPa for 0.5-2 hours to obtain an oriented carbon nanofilm with a thickness of 2-200 μm and a planar thermal conductivity of 80-3000 W / m·K; an adhesive is coated on the surface of the oriented carbon nanofilm by printing or dispensing , forming active points, then stretching the elastomer at a stretching rate of 0.01-10m / min, then combining the elastomer with the oriented carbon nanofilm through the bonding effect of the active points, and then shrinking the elastomer to form a vertically oriented structure film; removing the elastomer to obtain a high thermal conductivity electromagnetic shielding carbon nanofilm with a vertically oriented structure; the high thermal conductivity electromagnetic shielding carbon nanofilm has a thickness of 2-5000μm, a vertical thermal conductivity of 10-800W / m·K, and an electromagnetic shielding performance of 10-90dB at 10MHz-100GHz. The carbon nanofilm has a single component, which is not conducive to the study of electromagnetic shielding performance. Summary of the invention

[0008] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the technical problems of uncontrollable titanium oxide preparation process, difficult multilayer structure design, low absorption loss and narrow frequency band in titanium oxide-based electromagnetic shielding materials. The present invention provides a titanium oxide / carbon nanotube / graphene composite material and a preparation method and application. The method prepares a TiO2 / carbon nanotube / graphene precursor by a simple and clean hydrothermal reaction, and then obtains a Ti4O7 / carbon nanotube / graphene composite material by high-temperature heat treatment. Based on the strong interface polarization and defect polarization capabilities of Ti4O7, a high-efficiency electromagnetic wave shielding material with ultra-low reflectivity can be realized.

[0009] The first object of the present invention is to provide a method for preparing a titanium oxide / carbon nanotube / graphene composite material, comprising the following steps:

[0010] Dispersing isopropyl titanate, acetic acid, carbon nanotubes and graphene in anhydrous ethanol, and mixing them evenly to obtain a mixed solution;

[0011] The mixed solution is transferred to a reaction kettle and kept at 160-200°C for 4-8 hours to obtain a precursor;

[0012] The precursor is placed in a hydrogen atmosphere at 900-1200° C. for 2-8 hours to obtain a titanium oxide / carbon nanotube / graphene composite material.

[0013] Preferably, the mass ratio of isopropyl titanate, carbon nanotubes and graphene is 1:0.01-2:0.01-2.

[0014] Preferably, the volume ratio of the acetic acid to anhydrous ethanol is 1:4-12.

[0015] Preferably, the heating rate when preparing the precursor is 5-10° / min; the heating rate of the precursor in a hydrogen atmosphere is 1-2° / min.

[0016] The second object of the present invention is to provide a titanium oxide / carbon nanotube / graphene composite material.

[0017] The third object of the present invention is to provide an application of a titanium oxide / carbon nanotube / graphene composite material in the preparation of an electromagnetic shielding composite material.

[0018] A fourth object of the present invention is to provide a method for preparing a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material, characterized in that it comprises the following steps:

[0019] The titanium oxide / carbon nanotube / graphene composite material is mixed with polyvinylidene fluoride and polyvinylidene fluoride copolymer, respectively, and Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film and Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film are obtained by hot pressing.

[0020] The obtained Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film and Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film are hot pressed to form a sandwich structure electromagnetic shielding film, wherein the upper and lower layers are both Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film, and the middle layer is Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film;

[0021] The sandwich structure electromagnetic shielding film is prepared by supercritical foaming to obtain a sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material.

[0022] Preferably, the usage ratio of the polyvinylidene fluoride to the Ti4O7 / carbon nanotube / graphene composite material is 4-10wt%:1wt%; the usage ratio of the polyvinylidene fluoride copolymer to the Ti4O7 / carbon nanotube / graphene composite material is 4-10wt%:1wt%.

[0023] A fifth object of the present invention is to provide a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material.

[0024] A sixth object of the present invention is to provide an application of a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material in electromagnetic shielding.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a titanium oxide / carbon nanotube / graphene composite material and a preparation method and application. The present invention prepares a sandwich structure Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material. Compared with the method of preparing a carbon-based electromagnetic shielding composite film or a carbon-based electromagnetic shielding composite foam in the prior art, in the sandwich structure Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material prepared by the present invention, the upper and lower layers of Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding films provide efficient reflection shielding performance, and the middle layer of Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding foam has a conductive porous structure, which can effectively adjust impedance matching, reduce the surface electromagnetic wave reflectivity, and improve the electromagnetic wave absorption capacity. At the same time, adding one-dimensional carbon nanotubes to the three-dimensional structure can more effectively improve its structural continuity and enhance the transmission of electrons, thereby effectively attenuating electromagnetic wave energy. Therefore, the special sandwich structure film / foam / film can achieve efficient electromagnetic shielding performance with ultra-low reflectivity.

[0027] The present invention first prepares TiO2 / carbon nanotube / graphene precursors through a simple and clean hydrothermal reaction, then obtains Ti4O7 / carbon nanotube / graphene composite materials through high-temperature heat treatment, and finally prepares sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite materials through hot pressing and supercritical foaming technology. Figure 2 In the TiO2 / carbon nanotube / graphene precursor, round TiO2 nanoparticles are uniformly wrapped on the surface of carbon nanotubes and graphene, wherein the size of TiO2 is between 5 and 10 nm, the diameter and length of the carbon nanotubes are 20 nm and 1 to 10 μm respectively, and the diameter of the graphene is between 0.5 and 1 μm; in addition, Figure 3 It can be seen that the Ti4O7 particles in the Ti4O7 / carbon nanotube / graphene composite material obtained by hydrogen reduction undergo high-temperature melting and grow, and the particle size is between 50 and 100 nm.

[0028] The present invention applies Ti4O7-based electromagnetic shielding composite materials to the field of electromagnetic shielding materials for the first time, because high conductivity helps to form a higher imaginary part value of dielectric constant, indicating that it has a larger dielectric loss, and Ti4O7 has a stronger interface polarization and defect polarization ability, which can realize a highly efficient electromagnetic wave shielding material with ultra-low reflectivity. The present invention effectively improves the impedance matching and electromagnetic attenuation characteristics of the sandwich structure Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material by regulating the content ratio of Ti4O7, carbon nanotubes and graphene, and can be widely used as an electromagnetic shielding material in the corresponding electromagnetic protection and microwave stealth fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray diffraction pattern of the Ti4O7 / carbon nanotube / graphene composite sample.

[0030] Figure 2 This is a scanning electron microscope photo of the TiO2 / carbon nanotube / graphene composite sample.

[0031] Figure 3 This is a scanning electron microscope photo of the Ti4O7 / carbon nanotube / graphene composite sample.

[0032] Figure 4 Schematic diagram of electromagnetic shielding of sandwich structure Ti4O7 / carbon nanotube / graphene composite material.

[0033] Figure 5 Schematic diagram of the comparison of the average total shielding, reflection and absorption values ​​of the sandwich structure Ti4O7 / carbon nanotube / graphene composite material.

[0034] Figure 6 This is a flow chart for the preparation of sandwich structure Ti4O7 / carbon nanotube / graphene composite materials.

[0035] In the figure: 1 is the diffraction peak curve of ICSD#97-001-6297 card corresponding to Ti4O7 sample; 2 is the X-ray diffraction diagram of Ti4O7 / carbon nanotube / graphene composite sample; 3 is the X-ray diffraction peak curve corresponding to TiO2 / carbon nanotube / graphene composite sample; 4 is the electromagnetic shielding performance of Ti4O7 / carbon nanotube / graphene composite film in the 8.2-12.4GHz band; 5 is the electromagnetic shielding performance of sandwich structure Ti4O7 / carbon nanotube / graphene composite material in the 8.2-12.4GHz band; 6 is the average total shielding, reflection and absorption values ​​of Ti4O7 / carbon nanotube / graphene composite film in the 8.2-12.4GHz band; 7 is the average total shielding, reflection and absorption values ​​of sandwich structure Ti4O7 / carbon nanotube / graphene composite material in the 8.2-12.4GHz band. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0037] The purpose of the present invention is to provide a titanium oxide / carbon nanotube / graphene composite material, which is mainly based on the composite of Ti4O7 ceramic particles with high dielectric properties and carbon materials (such as carbon black, graphene and CNT) can effectively improve the material impedance matching and multiple loss mechanisms, thereby obtaining a Ti4O7 / carbon material (graphene, carbon black, carbon nanotube) electromagnetic shielding material with excellent shielding performance.

[0038] In order to achieve the above object, the present invention provides a first aspect of a method for preparing a titanium oxide / carbon nanotube / graphene composite material, comprising the following steps:

[0039] Dispersing isopropyl titanate, acetic acid, carbon nanotubes and graphene in anhydrous ethanol, and mixing them evenly to obtain a mixed solution;

[0040] The mixed solution is transferred to a reaction kettle and kept at 160-200°C for 4-8 hours to obtain a precursor;

[0041] The precursor is placed in a hydrogen atmosphere at 900-1200° C. for 2-8 hours to obtain a titanium oxide / carbon nanotube / graphene composite material.

[0042] The precursor prepared by the present invention is a TiO2 / carbon nanotube / graphene precursor, which is mainly prepared by a simple and clean hydrothermal reaction, and then a Ti4O7 / carbon nanotube / graphene composite material is obtained by high-temperature heat treatment. It can be seen that titanium oxide is a Ti4O7 compound.

[0043] Wherein, the mass ratio of isopropyl titanate, carbon nanotubes and graphene is 1:0.01-2:0.01-2.

[0044] The volume ratio of the acetic acid to anhydrous ethanol is 1:4-12.

[0045] The heating rate when preparing the precursor is 5-10° / min; the heating rate of the precursor in a hydrogen atmosphere is 1-2° / min.

[0046] In one embodiment, a method for preparing a titanium oxide / carbon nanotube / graphene composite material comprises:

[0047] Step 1, preparing TiO2 / carbon nanotube / graphene mixed solution:

[0048] Disperse isopropyl titanate, acetic acid, carbon nanotubes and graphene in anhydrous ethanol and stir evenly to obtain a TiO2 / carbon nanotube / graphene mixed solution, wherein isopropyl titanate: carbon nanotube: graphene: acetic acid: anhydrous ethanol = 1 g: 0.01-2 g: 0.01-2 g: 5-10 mL: 40-60 mL.

[0049] Wherein, acetic acid is used to provide a weakly acidic environment to promote the decomposition of isopropyl titanate.

[0050] Step 2, preparing TiO2 / carbon nanotube / graphene precursor:

[0051] Transfer the TiO2 / carbon nanotube / graphene mixed solution obtained in step 1 to a high-pressure reactor. Transfer the solution to a polytetrafluoroethylene reactor. Transfer the reactor to a drying oven and heat it to 160-200°C at a heating rate of 5-10° / min; keep it warm for 4-8 hours to react the TiO2 / carbon nanotube / graphene mixed solution in the high-pressure reactor. After the insulation is completed, cool it to room temperature with the furnace. Take out the precipitate of the solution after the solvothermal reaction, wash and dry it to obtain a TiO2 / carbon nanotube / graphene precursor.

[0052] Step 3, preparing Ti4O7 / carbon nanotube / graphene composite material:

[0053] When preparing the Ti4O7 / carbon nanotube / graphene composite material, the TiO2 / carbon nanotube / graphene precursor obtained in step 2 is placed in a tube furnace, and hydrogen is introduced as a protective gas. The temperature is raised to 900-1200°C at a heating rate of 1-10°C / min, and the temperature is kept for 2-8 hours. After the heat preservation is completed, the furnace is cooled to obtain the Ti4O7 / carbon nanotube / graphene composite material.

[0054] The present invention can derive a series of non-stoichiometric titanium oxides with high conductivity by high temperature reduction of TiO2, and the general chemical formula thereof is Ti x O 2x-1 (1≤x≤10). On the one hand, in a hydrogen atmosphere, H2 reacts with the oxygen atoms on the surface of TiO2; on the other hand, carbon nanotubes / graphene can provide carbon thermal reduction, and the surface oxygen vacancies generated diffuse into the interior of the material, converting Ti 4+ Restored to low-priced Ti 3+ Because the shear plane formed by oxygen defects is connected to the adjacent TiO octahedron through a shared plane, free electrons can move in the Ti-O cut plane layer of the atomic shared plane, forming a free electron channel that conducts along the shear plane direction, while the Magnéli phase Ti n O 2n-1 The oxygen defect density of Ti4O7 is the highest, and this structure makes the conductive performance of Ti4O7 the most outstanding.

[0055] The second aspect of the present invention provides a titanium oxide / carbon nanotube / graphene composite material. The composite material is obtained by using Ti4O7 as a matrix and compounding carbon nanotubes and graphene on the matrix. The content of the matrix is ​​50-99wt.%, and the content of the carbon material is 50-1wt.%; the sum of the percentages is 100%. Among them, the carbon material includes carbon nanotubes and graphene.

[0056] The particle size of the carbon nanotube and graphene is 1-10 μm. The particle size of the Ti4O7 particles is 50-100 nm.

[0057] A third aspect of the present invention provides an application of a titanium oxide / carbon nanotube / graphene composite material in the preparation of an electromagnetic shielding composite material.

[0058] A fourth aspect of the present invention provides a method for preparing a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material, comprising the following steps:

[0059] The titanium oxide / carbon nanotube / graphene composite material is mixed with polyvinylidene fluoride and polyvinylidene fluoride copolymer respectively, and Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film and Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film are obtained by hot pressing.

[0060] The obtained Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film and Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film are hot pressed to form a sandwich structure electromagnetic shielding film, wherein the upper and lower layers are both Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film, and the middle layer is Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film;

[0061] The sandwich structure electromagnetic shielding film is prepared by supercritical foaming to obtain a sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material.

[0062] The amount ratio of the polyvinylidene fluoride to the Ti4O7 / carbon nanotube / graphene composite material is 4-10wt%:1wt%. The amount ratio of the polyvinylidene fluoride copolymer to the Ti4O7 / carbon nanotube / graphene composite material is 4-10wt%:1wt%.

[0063] It should be noted that polyvinylidene fluoride and polyvinylidene fluoride copolymers are commercial raw materials used directly and are not involved in the synthesis of the present invention.

[0064] The present invention sets the saturation temperature below the starting temperature (163°C) of PVDF crystal melting by mismatching the crystal melting temperatures of two grades of PVDF resin to avoid blistering of the film layer, while the PVDF copolymer layer can still be foamed. Through supercritical foaming, a sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material is constructed.

[0065] In one embodiment, a method for preparing a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material comprises:

[0066] The Ti4O7 / carbon nanotube / graphene composite material was coupled by electrostatic assembly in N,N-dimethylformamide (DMF) solution, and polyvinylidene fluoride (PVDF) was added and stirred evenly in DMF, and hot-pressed at 200°C to obtain the Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film;

[0067] The Ti4O7 / carbon nanotube / graphene composite material is coupled by electrostatic assembly in a DMF solution, and a PVDF copolymer is added and stirred evenly in the DMF, and a Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film is obtained by hot pressing at 200°C;

[0068] Based on the melting point difference between PVDF and PVDF copolymer, in the prepared sandwich structure Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding composite material, the upper layer and the lower layer are both Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding films, and the middle layer is Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film. Through supercritical foaming, the obtained Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film is placed in a high-pressure intermittent foaming chamber, filled with 2000psi supercritical carbon dioxide, saturated at 140°C for 30min, and after saturation, the gas is quickly released and quenched in an ice bath to obtain a sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material, that is, a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material.

[0069] The sandwich structure Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding composite material has a specific preparation process, including:

[0070] The 0.2 mm Ti4O7 / carbon nanotube / graphene / PVDF composite and the 1.6 mm Ti4O7 / carbon nanotube / graphene / PVDF copolymer composite were placed on a 2.0×15.8×20 mm 3The sandwich structure is formed by hot pressing, wherein the upper and lower layers are Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding films, and the middle layer is Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film. Through supercritical foaming, the sandwich structure Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film is placed in a high-pressure intermittent foaming chamber, filled with 2000psi supercritical carbon dioxide, saturated at 120-160℃ for 30min, and after saturation, the gas is quickly released and quenched in an ice bath to obtain a sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material.

[0071] The electromagnetic shielding film is a Ti4O7 / carbon nanotube / graphene electromagnetic shielding film formed by combining the carbon nanotube, graphene and Ti4O7 particles.

[0072] A fifth aspect of the present invention provides a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material.

[0073] A sixth aspect of the present invention provides an application of a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material in electromagnetic shielding.

[0074] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0075] Example

[0076] The titanium oxide / carbon nanotube / graphene composite material proposed by the present invention uses Ti4O7 as a matrix, and is obtained by compounding carbon nanotubes / graphene on the matrix through a solvent thermal reaction. The particle size of the Ti4O7 particles is 50-100nm, and the particle sizes of the carbon nanotubes and graphene are 1-10μm. The content of the matrix is ​​50-99wt.%, and the content of the carbon nanotube / graphene is 50-1wt.%; the sum of the percentages is 100%.

[0077] The composite electromagnetic shielding material is a sandwich structure Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material formed by compounding the carbon nanotube / graphene material with Ti4O7 particles through solvent thermal reaction, hydrogen reduction, hot pressing, and supercritical foaming technology. Figure 6 As shown, the specific preparation steps are as follows:

[0078] Step 1, preparing TiO2 / carbon nanotube / graphene mixed solution:

[0079] 1 g of isopropyl titanate, 0.5 g of carbon nanotubes, 0.5 g of graphene, 50 mL of anhydrous ethanol and 15 mL of glacial acetic acid were stirred together at 80°C for 1 h. After ultrasonic dispersion for 30 min, hydrochloric acid HCl was added dropwise to adjust the pH value to 2 to obtain a TiO2 / carbon nanotube / graphene mixed solution.

[0080] Step 2: Preparation of TiO2 / carbon nanotube / graphene precursor:

[0081] The TiO2 / carbon nanotube / graphene mixed solution was transferred to a polytetrafluoroethylene reactor, and the reactor was transferred to a drying oven, and the temperature was increased to 180°C at a heating rate of 8° / min; the temperature was kept for 6 hours to obtain a TiO2 / carbon nanotube / graphene precursor.

[0082] Step 3, preparing Ti4O7 / carbon nanotube / graphene composite material:

[0083] When preparing the Ti4O7 / carbon nanotube / graphene composite material, the TiO2 / carbon nanotube / graphene precursor is placed in a tube furnace, hydrogen is introduced as a protective gas, the temperature is raised to 1000°C at a heating rate of 2° / min, and the temperature is kept for 4 hours. After the temperature is kept, the furnace is cooled to obtain the Ti4O7 / carbon nanotube / graphene composite material.

[0084] Step 4, preparing a sandwich structure Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material:

[0085] The Ti4O7 / carbon nanotube / graphene composite material was coupled by electrostatic assembly in N,N-dimethylformamide (DMF) solution, and polyvinylidene fluoride (PVDF) was added into DMF and stirred evenly, and then hot-pressed at 200°C to obtain the Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film.

[0086] The Ti4O7 / carbon nanotube / graphene composite material is coupled by electrostatic assembly in a DMF solution, and a PVDF copolymer is added and stirred evenly in the DMF, and a Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film is obtained by hot pressing at 200°C.

[0087] Based on the melting point difference between PVDF and PVDF copolymer, in the prepared sandwich structure Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding composite material, the upper layer and the lower layer are both Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding films, and the middle layer is Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film. Through supercritical foaming, the sandwich structure Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film is placed in a high-pressure intermittent foaming chamber, filled with 2000psi supercritical carbon dioxide, saturated at 140℃ for 30min, and after saturation, the gas is quickly released and quenched in an ice bath to obtain a sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material, that is, a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material.

[0088] The components of each example are shown in Table 1.

[0089] Table 1. Components of each example.

[0090]

[0091] The process parameters of each embodiment are shown in Table 2.

[0092] Table 2 Process parameters of each embodiment

[0093]

[0094] In order to illustrate the relevant properties of the composite material provided by the present invention, it is described in conjunction with the accompanying drawings.

[0095] Figure 1 This is the X-ray diffraction pattern of the Ti4O7 / carbon nanotube / graphene composite sample provided in Example 1. Figure 1 In the figure, the curve indicated by 1 represents the diffraction peak curve of ICSD#97-001-6297 card corresponding to the Ti4O7 sample; the curve indicated by 2 represents the X-ray diffraction pattern of the Ti4O7 / carbon nanotube / graphene composite sample; the curve indicated by 3 represents the X-ray diffraction peak curve corresponding to the TiO2 / carbon nanotube / graphene composite sample.

[0096] Figure 1 It can be seen that the prepared Ti4O7 / carbon nanotube / graphene corresponds obviously to the standard diffraction peak, indicating that the prepared Ti4O7 / carbon nanotube / graphene composite sample contains the expected three phases of Ti4O7, carbon nanotube and graphene.

[0097] Figure 2 This is a scanning electron microscope photograph of the TiO2 / carbon nanotube / graphene composite sample provided in Example 1.

[0098] Figure 2 It can be seen that spherical titanium dioxide and carbon nanotubes are uniformly adsorbed on the surface of graphene sheets.

[0099] Figure 3 This is a scanning electron microscope photograph of the Ti4O7 / carbon nanotube / graphene composite sample provided in Example 1. Figure 3 It can be seen that after heat treatment, Ti4O7 is embedded in the graphene sheet and carbon nanotubes are grafted onto the surface of the graphene sheet.

[0100] Figure 4 Schematic diagram of electromagnetic shielding of the sandwich structure Ti4O7 / carbon nanotube / graphene composite material provided in Example 1. Figure 4 In the figure, curve 4 indicates the electromagnetic shielding performance of Ti4O7 / carbon nanotube / graphene composite film in the 8.2-12.4GHz band, and its maximum shielding effectiveness reaches 58.6dB; curve 5 indicates the electromagnetic shielding performance of sandwich structure Ti4O7 / carbon nanotube / graphene composite material in the 8.2-12.4GHz band, and its maximum shielding effectiveness reaches 70.5dB.

[0101] Figure 5 A schematic diagram comparing the average total shielding, reflection and absorption values ​​of the sandwich structure Ti4O7 / carbon nanotube / graphene composite material provided in Example 1. Figure 5 Among them, the curve pointed to by 6 represents the electromagnetic shielding performance of Ti4O7 / carbon nanotube / graphene composite film in the 8.2-12.4GHz band, and its average total shielding, reflection and absorption values ​​are 58.6dB, 35.3dB and 23.3dB respectively; the curve pointed to by 7 represents the electromagnetic shielding performance of sandwich structure Ti4O7 / carbon nanotube / graphene composite material in the 8.2-12.4GHz band, and its average total shielding, reflection and absorption values ​​are 70.5dB, 15.4dB and 55.1dB respectively.

[0102] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a titanium oxide / carbon nanotube / graphene composite material, characterized in that: The following steps are involved: Dispersing isopropyl titanate, acetic acid, carbon nanotubes and graphene in anhydrous ethanol, and mixing them evenly to obtain a mixed solution; The mixed solution is transferred to a reaction kettle and kept at 160-200°C for 4-8 hours to obtain a precursor; The precursor is placed in a hydrogen atmosphere at 900-1200° C. for 2-8 hours to obtain a titanium oxide / carbon nanotube / graphene composite material.

2. The method for preparing the titanium oxide / carbon nanotube / graphene composite material according to claim 1, characterized in that: The mass ratio of isopropyl titanate, carbon nanotubes and graphene is 1:0.01-2:0.01-2.

3. The method for preparing the titanium oxide / carbon nanotube / graphene composite material according to claim 1, characterized in that: The volume ratio of the acetic acid to anhydrous ethanol is 1:4-12.

4. The method for preparing the titanium oxide / carbon nanotube / graphene composite material according to claim 1, characterized in that: The heating rate when preparing the precursor is 5-10° / min; the heating rate of the precursor in a hydrogen atmosphere is 1-2° / min.

5. A titanium oxide / carbon nanotube / graphene composite material prepared by the method according to any one of claims 1 to 4.

6. Use of the titanium oxide / carbon nanotube / graphene composite material according to claim 5 in preparing an electromagnetic shielding composite material.

7. A method for preparing a titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material, characterized in that: The following steps are involved: The titanium oxide / carbon nanotube / graphene composite material according to claim 5 is mixed with polyvinylidene fluoride and polyvinylidene fluoride copolymer, respectively, and the Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film and the Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film are obtained by hot pressing. The obtained Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film and Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film are hot pressed to form a sandwich structure electromagnetic shielding film, wherein the upper and lower layers are both Ti4O7 / carbon nanotube / graphene / PVDF electromagnetic shielding film, and the middle layer is Ti4O7 / carbon nanotube / graphene / PVDF copolymer electromagnetic shielding film; The sandwich structure electromagnetic shielding film is prepared by supercritical foaming to obtain a sandwich structure film / foam / film Ti4O7 / carbon nanotube / graphene electromagnetic shielding composite material.

8. The method for preparing the titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material according to claim 7, characterized in that: The usage ratio of the polyvinylidene fluoride to the Ti4O7 / carbon nanotube / graphene composite material is 4-10wt%:1wt%; the usage ratio of the polyvinylidene fluoride copolymer to the Ti4O7 / carbon nanotube / graphene composite material is 4-10wt%:1wt%.

9. A titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material prepared by the method according to claim 7 or 8.

10. Use of the titanium oxide / carbon nanotube / graphene electromagnetic shielding composite material according to claim 9 in electromagnetic shielding.